Investigating the relationship between playing violent video games and viewing violent TV programmes and aggressive behaviour among pre-teens - Kong, Luo Lan; Abdullah, Maria Chong; Roslan, Samsilah (Universiti Putra Malaysia Press, 2013)
This study aimed to investigate the relationship between the playing of violent video games and the viewing of violent TV programmes and aggressive behaviour among pre-teens. According to McGahee, Kemp and Tingen (2000), pre-teens referred to preadolescent children who are usually between 9 and 12 years of age. A total of 450 pre-teens aged 11 were randomly selected from nine schools in the state of Selangor, Malaysia, to participate in this study. This study employed a correlation research design and the data were analysed using both descriptive and inferential statistics to address the research objectives. The data were analysed to identify the top 10 favourite video games played by pre-teens in this study. Eight out of 10 video games played by pre-teens were found to be violent in nature. In addition, the top 10 favourite violent TV programmes viewed by pre-teens in this study were also identified. Findings from this study showed that there was a significant difference in the mean score of playing violent video games [t(257)=6.979, p<0.01] and viewing violent TV programmes [t(440)=3.544, p<0.01) between boys and girls who participated in the study. Moreover, the results from this study revealed there was a significant and positive relationship between playing violent video games (r=0.167, p<0.01), viewing violent TV programmes (r=0.126, p=0.000) and aggressive behaviour demonstrated by pre-teens. Multiple regression analysis showed that 39.4% of the variances in pre-teen physical aggression could be explained by both the playing of violent video games and the viewing of violent TV programmes, with the playing of violent video games as a stronger predictor of physical aggressive behaviour in pre-teens (ÃŸ=0.238, p=0.025).